PENERAPAN TEKNIK FORCE FIELD ANALYSIS (FFA) DALAM PERENCANAAN PROGRAM KESEHATAN - Eddy Siswanto (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
Planning is important part of conducting health program in community. Many techniques could be used in planning process. Force Field Analysis (FFA) was a tool to describes and analyzes the driving forces versus restraining forces of a proposed action or intervention. Based on FFA, the team would determine whether the proposed action was better to be continued or not. Participants of AMTC also used it to plan community-based health program. Otherwise, by using FFA, health team could plan better of health program, based on potentials and forces in community.